Effect of different application forms of efficient microorganisms on the agricultural productive of two bean cultivars - Calero Hurtado, Alexander [UNESP] (2019)
The use of Efficient Microorganisms (EM) can be an effective alternative to improve plant growth and yield in the bean cultivation. Therefore, different forms of application of efficient microorganisms were evaluated in the production of two cultivars of the common bean from November of 2013 to March of 2014. Two factors were studied; the first one was comprised of the two cultivars, Velazco Largo (VL) and Cuba Cueto (CC-25-9-N). The second factor consisted of four treatments with EM; without EM (control), soil inoculation (100 mL L-1), foliage applications (100 mL L-1), and the combined soil inoculation (100 mL L-1) plus foliar applications (100 mL L-1). The experiment was carried out in a randomized block design, in factorial outline 2×4, with three repetitions. The agronomic indicators were evaluated as the number of leaves per plant, the height of plants, number of pods per plant, number of seeds per pod, the mass of 100 seeds (g) and the yield (t ha-1). The results showed that the different forms of application of efficient microorganisms stimulated the agronomic indicators evaluated in both crops. The associated applications between the inoculation of the soil and foliage applications of efficient microorganisms provided better results, producing increments in the yield of 1.13 t ha-1 in VL and 2.15 t ha-1 in CC-25-9-N.